Analysis of Zakat Management Performance Based on The National Zakat Index Approach: A Case Study - Irni Nuraini (Islamic Social Finance, 2022)
Poverty is a sunnatullah. Islam focuses on poverty alleviation by laying the foundations of worship in the pillars of Islam in the form of social finance, namely zakat. In 2013, the National Zakat Potential reached Rp 217 trillion per year, but the realization was only around 1%. One of the leading causes of the low completion of zakat is the need for more public trust in the distribution of zakat through zakat institutions. Thus, it is necessary to assess the performance indicators of zakat management institutions to be published to the public. This study aims to assess and evaluate the performance of zakat management, including macro and micro dimensions, with a case study of LAZ Darut Tauhid (DT) Peduli Garut Regency. The sample used was 100 mustahik households using a purposive sampling technique. The analysis method used is the National Zakat Index using the Multi-Stage Weight Index estimation method. The results showed that the performance of zakat management by LAZ DT Peduli Garut is good, with the national zakat index value of 0.65 and the modified national zakat index value is 0.76.